Sewer processes : microbial and chemical process engineering of sewer networks - Hvitved-Jacobsen, Thorkild; Vollertsen, Jes.; Nielsen, AsbjrnHaaning (Boca Raton, FL : CRC Press, 2013)
'This extensively revised and updated second edition presents major revisions of several chapters, reflecting the theoretical and practical knowledge that has been gained since the publication of the previous edition a decade ago. In addition, it supplies new chapters on advanced modeling of sewer processes and gas phase control. It also includes greatly expanded coverage of odor formation and prediction, as well as of concrete corrosion caused by hydrogen sulfide. The book is written for graduate students, researchers, and industry professionals'--
Includes bibliographical references and index.
Keywords: Sewage -- Microbiology; Sewage -- Analysis; Sewerage -- Design and construction